Assessment of ethanol tolerance of Kluyveromyces marxianus CCT 7735 selected by adaptive laboratory evolution - Silveira, Fernando Augusto da (2018)
Whey is a by-product formed during the cheese-making, which presents lactose (4.5-5% w/v), soluble proteins, lipids, mineral salts and other components. It is the most abundant liquid waste generated in the dairy industries, which can lead to the pollution of water bodies due to its high biochemical oxygen demand and chemical oxygen demand. Whey permeate (WP) is a by-product constituted by lactose, produced from whey ultrafiltration. This way, WP can be converted by lactose-assimilating microorganisms, like yeasts, into value-added products. Kluyveromyces marxianus CCT 7735 has been showing a great potential for producing ethanol from lactose. However, its low ethanol tolerance is a drawback to be overcome, i. e., its growth is highly inhibited from 4% of ethanol (v/v). Adaptive laboratory evolution was used to select ethanol-tolerant K. marxianus CCT 7735 strains (ETSs). ETSs were grown under ethanol stress (4%, v/v) for long periods of time, over many generations (310-340 number of generations), in order to select the ethanol-tolerant phenotypes. From the determination of the physiological parameters, ETSs did not present alterations in their fermentative capacity, when compared their parental strains. However, ETS4 strain stood out for displaying a specific growth rate higher than the parental strain under ethanol stress (above 100%) and a specific ethanol production rate superior to all strains evaluated in this work. The metabolomic and fatty acids analysis were carried out with both ETS4 and parental strains to gain insights into the mechanisms related to the acquisition of ethanol tolerance. The accumulation of some amino acids (glutamate, alanine, valine, proline, and leucine) and metabolites of the citric acid cycle (isocitric acid, citric acid, cis-aconitic acid and malic acid) in ETS4 was found to be associated with the acquisition of ethanol tolerance. Furthermore, high fatty acids content and ergosterol in ETS4 compared to the parental strain indicate differences in their plasma membrane composition, which is consistent with metabolite leakage observed in the parental strain. Therefore, the accumulation of amino acids and citric acid cycle metabolites, as well as the alteration in the fatty acid and ergosterol contents contributed to the acquisition of ethanol tolerance in K. marxianus.